2010
DOI: 10.1007/s10681-010-0297-6
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming pre-fertilization barriers in the wide cross between Chrysanthemum grandiflorum (Ramat.) Kitamura and C. nankingense (Nakai) Tzvel. by using special pollination techniques

Abstract: In our earlier study, pre-fertilization barrier was one of the main factors causing the failure of the wide hybridization between Chrysanthemum grandiflorum 'Yuhuaxingchen' and C. nankingense, and seriously restricted the utilization of the excellent chrysanthemum germplasm, C. nankingense. In order to overcome the pre-fertilization barrier and obtain some hybrids, we carried out wide hybridization between them again in this study, and tentatively adopted three pollination techniques including mentor pollen, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 18 publications
1
26
0
Order By: Relevance
“…Therefore, delayed or repeated pollination is effective to overcome prezygotic cross-incompatibility in these crosses. These pollination methods have also been reported to be useful in overcoming prefertilization incompatibility in Chrysanthemum grandiflorum and Solanum lycopersicon (Zhang 2009, Sun et al 2011, Yan et al 2009). It could be concluded that there was no difference of cross-compatibility before fertilization no matter whether the male fertile or CMS line was hybridized as the maternal parent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, delayed or repeated pollination is effective to overcome prezygotic cross-incompatibility in these crosses. These pollination methods have also been reported to be useful in overcoming prefertilization incompatibility in Chrysanthemum grandiflorum and Solanum lycopersicon (Zhang 2009, Sun et al 2011, Yan et al 2009). It could be concluded that there was no difference of cross-compatibility before fertilization no matter whether the male fertile or CMS line was hybridized as the maternal parent.…”
Section: Discussionmentioning
confidence: 99%
“…However, hybrids always fail to be created because of cross-incompatibility, leading to the potentially usable germplasm in Nicotiana remained largely unexploited (Laskowska and Berbec 2005). Numerous efforts have been made to increase interspecific cross-compatibility, such as bud-stage pollination, delayed pollination, repeated pollination, mentor pollination and bridge cross (VanTuyl et al 1988, Somta et al 2006, Sun et al 2011, which have been effective in improving cross-compatibility in many plants.…”
mentioning
confidence: 99%
“…Additionally advances in high-throughput genotyping have markedly reduced the value per data point of molecular markers and increasing genome coverage. This reduction was in the main the results of three parallel developments [2] (i) the invention of huge numbers of single nucleotide polymorphism (SNP) markers in several species; (ii) development of high-throughput technologies, like multiplexing and gel-free deoxyribonucleic acid arrays, for screening SNP polymorphisms; and (iii) automation of the marker-genotyping method, together with efficient procedures for deoxyribonucleic acid extraction [2]. Phenotyping prices are increased Genotyping prices are being reduced and marker densities are being increased speedily.…”
Section: Need Of Genomic Selectionmentioning
confidence: 94%
“…The prediction accuracy of the GEBVs is evaluated by the correlation between the GEBVs and empirically estimated breeding values, r(GEBV: EBV), where the EBV can be obtained in a number of ways, most simply, as a phenotypic mean. This correlation provides an estimate of selection accuracy and thus directly relates GEBV prediction accuracy to selection response [2]. Other statistics such as mean-square error (MSE) are used occasionally [3].…”
Section: Genomic Selection Prediction Accuraciesmentioning
confidence: 99%
See 1 more Smart Citation